Palaeoenvironmental Interpretation of the Upper Triassic Baluti Formation in two selected sections at Amediya District, Kurdistan Region- Iraq: Insights from Palynofacies Study - Azo, Nahida M.; Hanna, Majeed T.; Edilbi, Ayad N. F. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Palynofacies analysis was carried out on 28 outcrop samples from the Upper Triassic Baluti Formation from Zewa and Sararu Sections in south and northwestern of Amediya District respectively, Kurdistan Region- Iraq. Based on the studied palynofacies, both sections are quite different in terms of depositional environment. Four types of palynofacies were recognized as following: the palynofacies type IV (Pl.1) is observed in the lower, middle and upper portions of upper part of Zewa Section in which, is characterized by high amount of phytoclasts, medium percentage of amorphous organic matter (AOM) and palynomorphs. This facies is referred to a depositional area that is located relatively nearshore with an arid hinterland, the palynofacies type V (Pl.2) was observed in lowermost and middle portions of upper part of Zewa Section, which is characterized by high domination of palynomorphs (mainly bisaccates and monosaccate pollen grains) and a less amount of phytoclasts and AOM. This facies indicates the domination of shallow marine to continent environment. The palynofacies type VI (Pl.3) was observed in middle and upper portions of upper part of the Zewa Section and lower and upper parts of the Sararu Section. This facies showed less amount or absence of palynomorphs, and relatively high amount of AOM and phytoclasts. In addition to this, a remarkable percentage of dinoflagellate cysts in Sararu Section has been found in this facies. This facies indicates proximal suboxic-anoxic shelf, and palynofacies type IX (Pl.4) was observed in middle to upper part of Sararu Section and characterized by less amount or absence of palynomorphs with high amounts of AOM and phytoclasts, which represents a deep environment of deposition.
Keywords: Baluti Formation; Kurdistan Region; Palynofacies; Depositional Environment; Sedimentary Organic Matter